Analisis Good Corporate Governance (GCG) Dan Biaya Utang Dalam Ekonomi Syariah (Bank Umum Syariah Tahun 2015-2018) - Anas Malik (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2020)
The effective interest rate that must be paid to creditors is often referred to as the cost of debt or the cost of debt. The right decision must be made by a manager in determining the cost of debt. if the debt is too large, it will result in an increase in interest costs which will have an impact on the soundness of the Bank. So that the implementation of corporate governance is then considered as the best management in decision making by managers and company management effectively and efficiently and in other ways to reduce the level of information asymmetry between company stakeholders. The main problem in this study is whether Good Corporate Governance (GCG) has an influence on the cost of debt in the view of Islamic economics. This study aims to determine whether the composite value on the GCG self-assessment report has an influence on the cost of debt and how Good Corporate Governance (GCG) and the cost of debt are in the perspective of Islamic economics. The value of the tcount is 1.277 and the significance value is 0.207, indicating that the results of the hypothesis test in the independent variable do not significantly affect the dependent variable on the cost of debt.